Unconventional Imaging, Sensing, and Adaptive Optics 2023 2023
DOI: 10.1117/12.2676719
|View full text |Cite
|
Sign up to set email alerts
|

Branch-point detection using a Shack-Hartmann wavefront sensor

Matthew Kalensky,
Denis Oesch,
Timothy J. Bukowski
et al.

Abstract: In this paper, two methods for identifying branch points from Shack–Hartmann wavefront sensor (SHWFS) measurements were studied; the circulation of phase gradients approach and the beam-spread approach. These approaches were tested using a simple optical-vortex model, wave-optics simulations, and with experimental data. It was found that these two approaches are synergistic regarding their abilities to detect branch points. Specifically, the beam-spread approach works best when the branch point is located towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It has recently been shown that when shock-wave-induced phase discontinuities 38,41 as well as branch-point-induced phase vortices 34,42,43 are located within the SHWFS subaperture lenslet pupils, there is appreciable beam spreading in the resultant image-plane irradiance patterns. Therefore, it is also expected that if sharp shear-layer-induced phase gradients intersected the SHWFS subaperture pupils, and the SHWFS lenslet resolution is coarse, similar localized beam spreading would be observed.…”
Section: Beam-spread Approachmentioning
confidence: 99%
“…It has recently been shown that when shock-wave-induced phase discontinuities 38,41 as well as branch-point-induced phase vortices 34,42,43 are located within the SHWFS subaperture lenslet pupils, there is appreciable beam spreading in the resultant image-plane irradiance patterns. Therefore, it is also expected that if sharp shear-layer-induced phase gradients intersected the SHWFS subaperture pupils, and the SHWFS lenslet resolution is coarse, similar localized beam spreading would be observed.…”
Section: Beam-spread Approachmentioning
confidence: 99%
“…Similar to computational wave-optic simulations [37,Chapter 9], we can also command repeatable high-resolution phase screens to the reflective LcPMs with the proper path-integrated Kolmogorov statistics (both spatial and temporal). Since deep-turbulence conditions can provide Greenwood frequencies on the order of 1 kHz for some beam-control applications [1-4], this scaled-laboratory setup does not allow for realtime demonstrations since the max framerates for the commercial-off-the-shelf LcPMs are on the order of 100 Hz for visible light; however, it does provide a flexible scaled-laboratory environment in which to test novel beam-control solutions, such as those which use branchpoint-tolerant phase reconstructors [38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…5 Conversely, a new approach that utilizes a subaperture irradiance pattern beam spread to identify branch points has recently been introduced. 32,33 Although other approaches exist, [34][35][36][37][38] these two approaches are the ones emphasized in this paper. Here, the circulation of phase gradients approach and beam-spread approaches are compared using a simple optical-vortex model, wave-optics simulations, and experimental data.…”
mentioning
confidence: 99%